Justicia global: sus implicaciones para el manejo de las inequidades en salud (2013)
ABSTRACT: The discussion on global justice, i.e. the discussion on the transformation of the economic and political relationships between the richest and poorest societies, is vital for public health today for two reasons. First, because there is a well-documented increase in health inequalities which resulted from the process of economic globalization; and second, because two approaches for managing these health inequalities have become particularly visible and are fully related to the field of work of social health: the social determinants of health approach, proposed by the who, and the social determination of health approach proposed by Latin American Social Medicine. In this sense, this paper aims to analyze the views on global justice that each of these approaches adopts as well as their proposals for managing the health inequities that are generated in each case. We concluded that the texts of the who Commission on Social Determinants of Health do not question or demand a change in the global economic and political relationships, whereas Latin American Social Medicine considers that, in order to advance in the elimination of global inequalities, an ethical questioning and a global restructuring of the power relationships are mandatory.